( a + 1 ) ( b + 1 ) ( c + 1 ) ( a 1 + 1 ) ( b 1 + 1 ) ( c 1 + 1 )
Let a , b and c be positive numbers. Find the minimum value of the expression above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Use Holder's inequality...
( a + 1 ) 6 1 ( b + 1 ) 6 1 ( c + 1 ) 6 1 ( a 1 + 1 ) 6 1 ( b 1 + 1 ) 6 1 ( c 1 + 1 ) 6 1 ≥ 6 a b c a b c + 6 1
Giving us 6 ( a + 1 ) ( b + 1 ) ( c + 1 ) ( a 1 + 1 ) ( b 1 + 1 ) ( c 1 + 1 ) ≥ 2
Raising both sides to the 6th power gives us
( a + 1 ) ( b + 1 ) ( c + 1 ) ( a 1 + 1 ) ( b 1 + 1 ) ( c 1 + 1 ) ≥ 6 4 .
We want a+1,b+1&c+1 to be minimum. Since a,b and c are positive, we have a=b=c=1, giving the value 64.
Problem Loading...
Note Loading...
Set Loading...
( a + 1 ) ( b + 1 ) ( c + 1 ) ( a 1 + 1 ) ( b 1 + 1 ) ( c 1 + 1 ) = ( a + 1 ) ( b + 1 ) ( c + 1 ) ( a 1 + a ) ( b 1 + b ) ( c 1 + c ) = ( a ( 1 + a ) 2 ) ( b ( 1 + b ) 2 ) ( c ( 1 + c ) 2 ) = ( a 1 + 2 + a ) ( b 1 + 2 + b ) ( c 1 + 2 + c ) By AM-GM inequality: a 1 + a ≥ 2 ≥ ( 2 + 2 ) ( 2 + 2 ) ( 2 + 2 ) = 6 4